How many melanomas might be prevented if more people applied sunscreen regularly?. (14th December 2017) - Olsen, C.M.; Wilson, L.F.; Green, A.C.; Biswas, N.; Loyalka, J.; Whiteman, D.C.
Summary: Background: Ultraviolet radiation causes cutaneous melanoma. Sunscreen prevents sunburn and protects skin cells against mutations. High‐quality epidemiological studies suggest regular sunscreen use prevents melanoma. Objectives: To calculate the potential impact fraction (PIF) for melanoma in the U.S.A. and Australia assuming a range of different intervention scenarios intended to increase sunscreen use. Methods: We calculated the PIF, the proportional difference between the observed number of melanomas arising under prevailing levels of sunscreen use compared with the number expected under counterfactual scenarios. We used published melanoma incidence projections for Australia and the white population in the U.S.A. from 2012 through to 2031 as the baseline condition, with estimates for protective effects of 'regular sunscreen use' from the literature. Sunscreen prevalence was sourced from national or state surveys. Results: Under a plausible public health intervention scenario comprising incremental increases in sunscreen prevalence over a 10‐year implementation programme, we estimated that cumulatively to 2031, 231 053 fewer melanomas would arise in the U.S. white population (PIF 11%) and 28 071 fewer melanomas would arise in Australia (PIF 10%). Under the theoretical maximum model of sunscreen use, almost 797 000 (PIF 38%) and approximately 96 000 (PIF 34%) melanomas would be prevented in the U.S.A. and Australia, respectively between 2012 and 2031. A sensitivity analysis using weaker effect estimates resulted in more conservative PIF estimates. Conclusions: Overall, interventions to increase use of sunscreen would result in moderate reductions in melanoma incidence, assuming no compensatory overexposure to the sun. Countries with a high incidence of melanoma should monitor levels of sunscreen use in the community. Abstract : What's already known about this topic? Sunscreen prevents sunburn and protects skin cells (including melanocytes) from mutations induced by ultraviolet radiation. Prospective cohort studies and one randomized trial suggest regular sunscreen use reduces risk of melanoma. Regular use of sunscreen is uncommon, even in populations residing in areas of high ambient sunlight levels. What does this study add? Under plausible scenarios of increasing prevalence of sunscreen use, cumulative incidence of melanoma between 2012 and 2031 could reduce by ˜10% in high‐incidence populations. Monitoring sunscreen use in populations is necessary to inform melanoma control efforts. Plain language summary available online Respond to this article